Plasmid DNA coding for influenza virus haemagglutinin induces Th1 cells and protection against respiratory infection despite its limited ability to generate antibody responses - MILLS, KINGSTON (Society for General Microbiology, 2000)
Direct intramuscular injection of plasmid DNA can generate immune responses against encoded antigens. However, the relative ability of DNA vaccines to induce cellular and humoral immunity after a single or booster immunization and the persistence of this response have not been fully elucidated. In this study, induction and maintenance of antibody and T cell subtypes with different doses of naked DNA encoding the haemagglutinin (HA) gene of influenza virus were examined and compared to the immune responses and protection induced by respiratory tract infection and immunization with a killed virus vaccine. Like natural infection, immunization with HA DNA induced potent Th1 responses. Spleen cells from mice immunized once with HA DNA in the dose range 10 ng to 100 ?g secreted significant levels of IFN-, but low or undetectable IL-5, in response to influenza virus in vitro. Furthermore, CD4+ HA-specific Th1 clones were generated from spleens of immunized mice. Although T cell responses waned 12 weeks after a single immunization, antigen-specific Th1 cells persisted in the spleen for at least 6 months after two booster immunizations. In contrast, influenza virus-specific ELISA IgG titres were low after a single immunization and required two booster immunizations to reach significant levels. Furthermore, haemagglutination inhibition (HI) antibodies were weak or undetectable after two immunizations. Nevertheless, two doses of HA DNA conferred almost complete protection against respiratory challenge with live virus. Thus, despite the limited ability to induce antibodies, DNA vaccines confer protective immunity against influenza virus infection, which appears to be mediated by Th1 cells.
PUBLISHED
Keywords: Biochemistry